Early Reduction of Pediatric Traumatic Posterior Hip Dislocation Is Much More Important Than the Treatment Procedure. Issue 11 (November 2019) - Yuksel, Serdar; Albay, Cem
Abstract : Abstract: Traumatic hip dislocations are very rare in the pediatric population, and they are real emergent cases that can occur with minimal trauma. If they are not diagnosed immediately and reduction is not performed as soon as possible, they may cause problems such as avascular necrosis and degenerative arthritis. Performing reduction within the first 6 hours is of vital importance. We aim to present the functional outcomes and radiographic results of 2 pediatric traumatic hip dislocation cases with 36 months of follow-up who were treated with abduction orthosis after the reduction. We want to emphasize the importance of reduction time in the outcome of posterior traumatic hip dislocations followed with abduction orthesis even if there is a trend and suggestion to treat these patients with spica cast with the review of the recent literature.